Effect of different copper fillers on the electrical resistivity of conductive adhesives - Li-Ngee, Ho; Nishikawa, Hiroshi; Takemoto, Tadashi (Springer Science+Business Media, LLC, 2011)
Link to publisher's homepage at http://www.springerlink.com